2017
DOI: 10.1186/s13023-017-0611-7
|View full text |Cite
|
Sign up to set email alerts
|

Health technology assessment of new drugs for rare disorders in Canada: impact of disease prevalence and cost

Abstract: BackgroundAuthors from the Canadian Agency for Drugs and Technologies in Health (CADTH) presented an analysis of submissions to the Common Drug Review (CDR) between 2004 and February 3, 2016 for drugs for rare disorders (disorders with a prevalence of <50 per 100,000).ObjectiveThe aim of this analysis was to examine the same CDR submissions to evaluate whether the negative reimbursement recommendation rate, clinical evidence of efficacy and statements concerning the drug’s cost in the CDR reports varied with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 3 publications
1
31
1
Order By: Relevance
“…A 2017 analysis of recommendations for rare disorder drugs indicates that an objective of the CADTH-pCPA integration is to ensure that a negative recommendation results in no pCPA negotiation, while a positive one sets up factors for inclusion in the negotiation (usually the need for a price reduction) between the pCPA and pharmaceutical manufacturer. 24 The analysis further demonstrated that a drug’s cost is associated with the likelihood of a negative CDR recommendation; for drugs used daily that had an estimated annual cost of less than CAN$55,000, the negative recommendation rate was 17%, compared with a rate of 74% for drugs costing more than CAN$55,000. 41…”
Section: Price Negotiations For Coverage In Canadian Public Drug Planmentioning
confidence: 98%
See 1 more Smart Citation
“…A 2017 analysis of recommendations for rare disorder drugs indicates that an objective of the CADTH-pCPA integration is to ensure that a negative recommendation results in no pCPA negotiation, while a positive one sets up factors for inclusion in the negotiation (usually the need for a price reduction) between the pCPA and pharmaceutical manufacturer. 24 The analysis further demonstrated that a drug’s cost is associated with the likelihood of a negative CDR recommendation; for drugs used daily that had an estimated annual cost of less than CAN$55,000, the negative recommendation rate was 17%, compared with a rate of 74% for drugs costing more than CAN$55,000. 41…”
Section: Price Negotiations For Coverage In Canadian Public Drug Planmentioning
confidence: 98%
“…CADTH does not publicly acknowledge having a cost-effectiveness ratio threshold for assessing drugs, but evidence exists to suggest that CAN$50,000 per quality-adjusted life-year, first proposed in the early 1990s, 23 is used although not consistently applied 18 , 19 (a higher threshold appears to be used where there are unmet therapeutic needs or a lack of alternative options and for rare disorder and oncology drugs). Negative recommendations are frequently based on the expert committee’s opinion that a drug’s efficacy evidence is inadequate 19 , 24 despite having been assessed by Health Canada’s regulatory review as acceptable. While regulatory and HTA reviews have different objectives, 25 this can result in CADTH’s committees duplicating work already done by the federal agency.…”
Section: Drug Reimbursement Recommendation Processes In Canadamentioning
confidence: 99%
“…Although many international HTA agencies have not established a definition of rarity (including an incidence and/or prevalence threshold), there is consistent recognition that rare diseases are often severe, chronic, seriously debilitating, degenerative, life threatening, with no real alternative treatment (17)(18)(19). However, as there is no universally accepted definition, we used incidence as a mechanism to operationalize rarity since it can be measured and quantified.…”
Section: Definition Of Raritymentioning
confidence: 99%
“…In a recent analysis of 55 CDR recommendations for 42 rare disorder drugs submitted between 2004 and February 2016, 11,12 18 reimbursement recommendations pertained to 16 drugs for rare disorders that commonly manifest during childhood (Table 1). Of the 18 reimbursement recommendations, 12 were negative.…”
Section: Ohip+ and The Ontario Public Drug Programs (Opdp) Recent Drumentioning
confidence: 99%